Pendampingan Belajar Operasi Hitung Matematika Dengan Menggunakan Metode Jaritmatika - Dwi Laila Sulistiowati; Jamilah (CV. Multi Kreasi Media, 2024)
Numeracy is one of the important materials for students to master in order to learn other materials. But unfortunately learning counting material is not an easy thing for students. Many students at MI Ma'arif 1 Kota Baru Utara have difficulty in performing counting operations. To overcome this, a method is needed that can make it easier for students to learn counting material, namely the jaritmatika method. Thus, this activity aims to improve students' understanding in performing addition, subtraction, multiplication and division counting operations by applying the jaritmatika method. The targets of this service activity are grade 3 students at MI Ma'arif 1 Kota Baru Utara. The method used is mentoring that trains them to use the jaritmatika method to improve their ability to perform counting operations. The results of this activity show that students' ability to perform counting operations can be improved by applying the jaritmatika method, both addition, subtraction, multiplication and division operations.